2014
DOI: 10.1371/journal.pone.0101578
|View full text |Cite
|
Sign up to set email alerts
|

Non-Selective Cation Channels Mediate Chloroquine-Induced Relaxation in Precontracted Mouse Airway Smooth Muscle

Abstract: Bitter tastants can induce relaxation in precontracted airway smooth muscle by activating big-conductance potassium channels (BKs) or by inactivating voltage-dependent L-type Ca2+ channels (VDLCCs). In this study, a new pathway for bitter tastant-induced relaxation was defined and investigated. We found nifedipine-insensitive and bitter tastant chloroquine-sensitive relaxation in epithelium-denuded mouse tracheal rings (TRs) precontracted with acetylcholine (ACH). In the presence of nifedipine (10 µM), ACH ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…In a previous study, we found that bitter-tasting chloroquine can inhibit cytosolic Ca 2+ elevations by blocking TRPC3 channels [25] and VDCCs in mouse airway smooth muscle cells [25,26]. In the present study, we explored whether chloroquine could inhibit Ca 2+ increases in T cells.…”
Section: Introductionmentioning
confidence: 91%
“…In a previous study, we found that bitter-tasting chloroquine can inhibit cytosolic Ca 2+ elevations by blocking TRPC3 channels [25] and VDCCs in mouse airway smooth muscle cells [25,26]. In the present study, we explored whether chloroquine could inhibit Ca 2+ increases in T cells.…”
Section: Introductionmentioning
confidence: 91%
“…However, our and others' results indicate that the relaxation would not be mediated by BKs, which will result from the inhibition of L-type voltage-dependent Ca 2+ channels (LVDCCs) and non-selective cat ion channels (NSCCs) [4][5][6][7]. These studies clarified the paradox about the mechanism of bitter Tastant-induced relaxation.…”
mentioning
confidence: 46%
“…However, the agonist ACH-induced the Ca 2+ release from the intracellular store mediated by IP 3 Rs will not be inhibited, thereby, which leads to a depletion of the store to activate SOC (store-operated channels) such as the NSCCs [6]. In addition, ACH (or methacholine) also activates LVDCCs [5,6].…”
mentioning
confidence: 99%
See 2 more Smart Citations